Salivary Parameters and Caries Indices in Children with Black Tooth Stains - (:unkn) unknown (JOURNAL PEDODONTICS INC, 2012)
Objective: Black tooth stain in children has been associated commonly with a low caries experience. The present study aimed to to compare salivary factors and caries indices in children with and without black tooth stain and to investigate the relationship between caries and caries associated salivary factors in these children. Study Design: Salivary flow rate, pH, buffering capacity, total calcium and phosphorus were determined. Calcium and phosphorus levels were assayed by Inductive Coupled Plasma with Atomic Emission Spectrometry. DMFT and dft indices were evaluated according to WHO criteria. Results: Significantly higher levels of salivary buffering capacity and calcium, and lower flow rate were found in children with black tooth stain compared with those of without black tooth stain (p < 0.01, p = 0.044 and p = 0.037, respectively). The differences in phosphorus and pH were not significant between the groups. The dft index was found to be significantly lower in children with black tooth stain than children without black tooth stain (p = 0.030). However, DMFT did not change between the groups. There is no relationship between salivary parameters and caries indices in children with black tooth stain. Conclusion: It is suggested that low caries tendency seen in children with black tooth stain may be associated with high salivary calcium and buffering capacity.
Keywords: black tooth stain; dental caries; saliva; children; DENTAL-CARIES